Los juegos ancestrales y tradicionales y capacidades coordinativas en los niños de 4 a 6 años de edad del sexo masculino y femenino de la escuela Yaguarzongo de la comunidad de Yukukapak del canton Saraguro en el período 2014 - Lozano Cango, Carlos Olmedo (2015)
When we talk about ancestral and traditional games, we are referring to a people or country culture because through this games we can say that apart of being funny we are rescuing traditions and customs of our ancestors and reconsidering that to recreate is the objective of all ancestral and traditional games very applicable for very young children. The basic coordinative capacities which try the fine coordination that are the eye, hand and brain, through fine motor we can determine the development age in children. To have control of the fine motor, children need to learn knowledge and planning, coordination, muscular strength, normal sensibility to develop the fine motor we used games like marbles, tops and hopscotch, even though this game are to develop the gross motor. The gross motor serves to manage big muscle groups and big movements like run, jump and throw. Also to develop the gross motor in the children we applied games such as greasily pole, bagged race, the chaskis, chopping wood and dancing. The investigation topic is: The ancestral and traditional games and the coordinative capacity of children under 4 and 6 years from the Yaguarzongo school, in the community Yukukapak from Saraguro city: Loja 204 whose problematic is The lack of usage of ancestral and traditional games which inhibits to improve the coordinative capacities in the children under 4 and 6 years that educate at Yaguarzongo school at Yukukapak community in Saraguro city; Loja 2014, with the objective ; to evaluate the knowledge of ancestral and traditional games of children that educate at Yaguarzongo school to improve the coordinative capacities, supporting with a methodology which allowed to diagnosis when we applied the survey, the plan of activities and the pre tex and post tex. Finally, we arrived to propose the conclusions and recommendations which are aligned to the local reality and will serve to develop the coordinative capacities through the usage of the ancestral and traditional games.